PERBEDAAN PENINGKATAN KADAR HEMOGLOBIN YANG MENGKONSUMSI TABLET FE DENGAN TABLET FE KOMBINASI VITAMIN C - Suparningsih, Ni Made Dwi (JURNAL MEDIA KESEHATAN, 2014)
According of Health Research Base (2013), prevalance of anemia in pregnancy (37,1%). The provision of iron tablets combination vitamin C increases of hemoglobin rate. Purpose of this study to known the difference in the enhancement of hemoglobin rate who consumed iron tablets with iron tablets combination vitamin C. This study used quasi experiment design. Samples in this study were 60. The measurement used hemoglobin digital. The analysis of data used dependent and independent test. Result of this study showed there was difference hemoglobin rate before and after treatments each the group with dependent test showed (p=0,000). Independent test showed (p=0,000), there were differences in the enhancement of hemoglobin rate between who consumed iron tablets with iron tablets combination vitamin C. Be expected health workers check the hemoglobin rate when the the fisrt trimester and third trimester, then provide vitamin C with iron tablets and also provide explanation of the types of foods that contain a lot of vitamin C.